Personality and risk of addiction to Internet in university students - Astonitas Villafuerte, Lya Mainé (2005)
The articles studies the frequency and purpose of Internet use, the indicators of risk for Internet addiction and the persona lit y of 66 university students from a private university in Lima. These variables are analyzed together with the dimensions and facets of the NEOPI-R, based in the big five model. An association was found between the facets values (04) and actions (06), which belong to the Openness dimension (O), and the risk of Internet addiction. A deeper analysis reveals a positive relationship between the number of symptoms of Internet addiction and the Neuroticism (N) dimensiono Additionally, there is a negative relationship between the number of symptoms and the Consciousness (C) dimension,especially on the facets self-discipline (CS), dutifulness (C3), achievement-striving (C4) and deliberation (C6).